ANALISIS SPC PADA PRODUKSI GENTENG DI UD. GENTENG MANTILI SDH KABUPATEN PRINGSEWU - Yosijanuardi, Yosi; Ayudyah Eka Apsari (Bajang Institute, 2024)
Problems in the production process at UD. Mantili Tile Sdh Pringsewu Districtcaused losses to the company and customers. From January to December 2023, theproduct defect rate reaches 13%, while the allowable production defect tolerancelimit is 7%. This high level of defects contributes to an increase in production costs.Therefore, this research is expected to reduce the level of production defects. Manyfactors cause defects, such as raw material quality, human error, and poorequipment condition, affecting productivity and product quality. By using theStatistical Process Control (SPC) method, it is expected to reduce the defect rate,identify the type of damage, and categorize the factors causing product defects. Dataprocessing using pareto charts shows that fracture defects are the most dominantwith a percentage of 53.1%, followed by crack defects at 46.9%. Analysis withfishbone diagrams reveals that the causative factors of disability consist of threemain elements: human, material, and method